Application level of electronic school administration in the post -education experience in light of the Corona pandemic (Covid-19) in the schools of Mafraq Governorate in the Hashemite Kingdom of Jordan - Daradkeh, Sayel Mohsen (Journal of Educational and Psychological Sciences, 2022)
The study aimed to reveal the level of e-learning management in schools in the province of Al-Mafraq under Corona pandemic (COVID-19) and to identify the constraints and difficulties faced by managers in using e-school management during the educational process under Corona pandemic (COVID-19), and the extent to which teaching staff interacted with the electronic school system in the schools of the Ministry of Education and how the students interacted with the electronic school system of the Ministry of Education from the point of view of the teaching staff.This study based its procedures on the analytical descriptive approach and the study and analysis of management cadre responses.The area of "continuity of the electronic learning system in the Corona population" (COVID-19) in schools in the province of Al-Mafraq ranged from a low to a medium degree.E-learning disabilities have ranged from a low degree to a high degree, due to living conditions.The interaction of teaching staff with the Electronic Administration under the Corona spread (COVID-19) ranged from low to high.The results indicated that the area of student interaction with e-learning under the Corona spread (COVID-19) was moderate, and that their interaction in some e-learning activities ranged from medium to low.This study recommends that positive guidance for students and teaching staff members be invested in e-education, plans and programmes to benefit from such guidance, and e-school training courses for both students and teaching staff.Provide an appropriate learning environment for the application of e-learningl.This study has been divided into three chapters and a conclusion.
Keywords: Electronic school administration; Corona virus (Covid-19); distance education